Development of Aluminium-Nickel Coated Short Carbon Fiber Metal Matrix Composites. (2018) - Kumar, Nithin; Chittappa, H.C.; Ezhil Vannan, S.
Abstract: Fiber reinforced composites have become a great boon ever since matrix and fibre are combined in macroscopic manner. Among them the metal matrix composites are unique because of their superior properties .The manufacturing of carbon fiber reinforced Aluminum Metal Matrix Composites [AMMCs] involves the formation of a brittle intermetallic phase due to the reaction taking place at the fiber-matrix interface at temperatures exceeding 700°C. To avoid this undesired chemical reaction that ultimately results in the degradation of composite properties, the reinforcement is coated with nickel by electro less process. This paper describes the Electroless Nickel [EN] coating process carried out on PAN based short carbon fibers. The resulting fibers are investigated for their metallographic characteristics by microscopy. These coated fibers were mixed with aluminium alloy by stir casting technique. The resulting composite's hardness and tensile strengths were studied